The searcher - French, Tana (Viking, an imprint of Penguin Random House LLC, 2020)
"Cal Hooper thought a fixer-upper in a bucolic Irish village would be the perfect escape. After twenty-five years in the Chicago police force and a bruising divorce, he just wants to build a new life in a pretty spot with a good pub where nothing much happens. But when a local kid whose brother has gone missing arm-twists him into investigating, Cal uncovers layers of darkness beneath his picturesque retreat, and starts to realize that even small towns shelter dangerous secrets"--